Comparison of a high-carbohydrate and high-protein breakfast effect on plasma ghrelin, obestatin, NPY and PYY levels in women with anorexia and bulimia nervosa - Sedlackova, Dana; Kopeckova, Jana; Papezova, Hana; Hainer, Vojtech; Kvasnickova, Hana; Hill, Martin; Nedvidkova, Jara (Nutrition & metabolism, 2012)
BACKGROUND: The present study investigated plasma levels of gut-brain axis peptides ghrelin, obestatin, NPY and PYY after consumption of a high-carbohydrate (HC) and high-protein (HP) breakfast in patients with anorexia nervosa, bulimia nervosa and in healthy controls. These peptides play an important role in regulation of energy homeostasis and their secretion is disturbed under condition of eating disorders. As various types of consumed macronutrients may induce different plasma hormone responses, so we examined these responses in women patients with eating disorders and compared them with those of healthy controls. METHODS: We examined plasma hormone responses to HC and HP breakfast in patients with AN (n = 14; age: 24.6 ± 1.8 years, BMI: 15.3 ± 0.7), BN (n = 15; age: 23.2 ± 1.7 years, BMI: 20.5 ± 0.9) and healthy controls (n = 14; age: 24.9 ± 1.4 years, BMI: 21.1 ± 0.8). Blood samples were drawn from the cubital vein, the first blood drawn was collected before meal, and then 30, 60, 90, 120 and 150 min after breakfast consumption. Plasma hormone levels were determined by commercially available RIA kits. RESULTS: Fasting and postprandial plasma obestatin levels were significantly increased in both AN and BN patients, while plasma ghrelin levels were significantly increased in AN patients only. After breakfast consumption, plasma levels of ghrelin and obestatin decreased, although they were still above the range of values of healthy controls. Fasting NPY plasma levels were significantly increased in AN and BN patients and did not change postprandially. Fasting PYY levels were comparable in AN, BN and healthy controls, but postprandially significantly increased after HP breakfast in AN and BN patients. Different reactions to breakfast consumption was found for ghrelin and PYY among investigated groups, while for obestatin and NPY these reactions were similar in all groups. CONCLUSIONS: Significant increase of obestatin and NPY in AN and BN patients may indicate their important role as the markers of eating disorders. Different reactions of ghrelin and PYY to breakfast consumption among groups suggest that role of these hormones in regulation of energy homeostasis can be adjusted in dependence to acute status of eating disorder.